Characterization and validation of postnatal murine precision cut lung slices using different approaches of stereology - Pérez Bravo, David; Justus Liebig University Giessen (My University, 2022)
Understanding the process of alveolarization is necessary, since it is key to develop new therapeutic strategies for pulmonary structural diseases. Unfortunately, in vivo approaches in mice often lead to lethal phenotypes and there are strong ethical concerns in the way of in vivo human studies of alveolarization. Therefore, the development of a suitable in vitro model to study alveolarization emerges as an attractive and indeed necessary alternative. The present study is aimed to characterize and validate current models of precision cut lung slices (PCLS) in postnatal mice to identify the best possible conditions to objectively validate structural changes upon in vitro alveolarization using stereology.
Keywords: ddc:570